Relaksasi Benson untuk Mengontrol Kadar Gula Darah Penderita DM di Wilayah Kerja Puskesmas Pahandut Palangka Raya - Aida Kusnaningsih (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
Diabetes mellitus is a metabolic disease characterized by an increase in blood glucose levels. One way to manage it is with Benson Relaxation. Benson Relaxation is a relaxation technique that is a combination of relaxation techniques with individual belief systems. Research shows that Benson relaxation can reduce blood glucose levels in DM patients. Community service activities by applying the results of the study namely Benson Relaxation to control blood sugar levels were carried out in 32 DM patients. Activities include health education about DM and Benson Relaxation and the practice of carrying out Benson's Relation accompanied by the sounds of the Asmaul Husna. The media used during the activity were LCD projector and IM3 Asmaul Husna. The event went smoothly according to the plan; all participants followed the movement enthusiastically from beginning to end. During the event, the media used during the activity can function properly, and the environment is quite conducive. The evaluation results of the participants were able to mention again about DM and its management and were able to practice Benson Relaxation well. The activity provided benefits in the form of increasing knowledge about Diabetes Mellitus and its management and the ability to carry out Benson Relaxation to control blood sugar levels in DM patients in the Pahandut Community Health Center Palangka Raya Benson work area.